Pakistani LIS scholars' altmetrics in ResearchGate. Issue 2 (4th July 2017) - Ali, Muhammad Yousuf; Richardson, Joanna
Abstract : Purpose: The purpose of this paper is to analyse the research performance of Pakistani library and information science (LIS) scholars, using the altmetrics provided by ResearchGate (RG). Design/methodology/approach: Purposive sampling was used to collect profiles between 15 January 2015 and 30 April 2016 of all members of RG who had self-identified as being an LIS scholar of Pakistani nationality. Additional demographic data were obtained through a small survey administered via Google Docs. Resultant data were analysed in SPSS Version 21. Findings: Study results were broadly consistent in terms of demographical data with previous studies of this cohort. There was a positive correlation between publications, reads, and citations for scholars who had recorded at least one publication. The majority of publications had not been published in a high impact factor journal. Academic networking site profiles create the potential for collaboration, building connections, and exchanging information. Research limitations/implications: Some scholars eliminated from this study may have published at least one output but neglected to upload details to RG. It is a purposive, exploratory study that provides insights into future research. Practical implications: The paper produces findings of relevance to researchers in other countries and/or disciplines who may wish to conduct a similar study of a defined cohort. Originality/value: There have been no previous published research studies on altmetrics associated with Pakistani LIS scholars.